Substitution de la présure animale par un autre coagulant d’origine végétale (chardon de marie, silybum marianum) (essai de coagulation sur différents lait). - AMROUNE, Meriem (My University, 2019)
The objective of this work is the extraction of vegetable rennet from the petals of the milk thistle (Silybum marianum) harvested from Ain Sefra, Naama, and the study of the possibility of their use as a rennet substitute. And also study the effect of the extract obtained on three types of milk (cow's milk from the farm, pasteurized cow's milk and reconstituted milk) and determine the dose that can coagulate the milk faster (10, 15, 20 or 25ml of the extract). The results obtained show that the coagulation time of cow's milk on the farm is faster than pasteurized cow's milk, whereas reconstituted milk coagulation is slower since it contains a protein level (2.05%) and less casein than other types of milks, which causes the increase in clotting time. In addition, it contains a lot of water and low in dry matter. It has been noticed when the coagulation time decreases, the strength of the rennet has increased. Finally, the results obtained converge towards the possibility of substitution of rennet by the extract of the milk thistle (Silybum marianum) in the coagulation of the milk. It could also be used in other fields or for techno-industrial purposes.
Keywords: milk; milk thistle petal; coagulant agent; coagulation; rennet substitute; hakka